Everyday stories of impact: interpreting knowledge exchange in the contemporary university. (26th November 2018) - Matthews, Peter; Rutherfoord, Robert; Connelly, Steve; Richardson, Liz; Durose, Catherine; Vanderhoven, Dave
Abstract : Research into the barriers of getting evidence produced by academics into policymaking processes has often highlighted the lack of research on academics and what they do, as compared to what policymakers do. This was most recently highlighted in a systematic review of the literature (Oliver et al, 2014). This paper reports on research carried out with academics who were tasked with producing evidence reviews for the UK Department for Communities and Local Government based on research funded by the UK Arts and Humanities Research Council. Using a novel co-produced methodology the academics were interviewed by an academic and a UK civil servant, with the analysis carried out by both. Using an interpretive approach, the findings identify specific meaning-making stories or practices that were enablers or barriers to producing evidence suitable for policymakers. The paper identifies three areas that affect academic behaviour at the nexus with policymaking: career biographies; disciplinary background; and the contradictory institutional pressures on academics. We conclude by arguing for a more collaborative approach between academics and policymakers. The co-produced approach also allowed us to identify the need for policymakers and civil servants to learn more about the different drivers of academics and the ways in which they work.